Application of Surface Click Reactions to Localized Surface Plasmon Resonance (LSPR) Biosensing. Issue 42 (10th July 2017) - Yaakov, Noga; Chaikin, Yulia; Wexselblatt, Ezequiel; Tor, Yitzhak; Vaskevich, Alexander; Rubinstein, Israel
Abstract: Localized surface plasmon resonance (LSPR) spectroscopy is an effective tool for sensitive, affordable, and label‐free biosensing. LSPR transducers based on nanoparticulate Au films have been applied to biosensing of receptor–analyte interactions, employing primarily thiolated receptors for constructing biorecognition interfaces on nanostructured Au surfaces. This popular method suffers from a major drawback, that is, the need to prepare a thiolated receptor for each system used, which is typically synthetically complex and time‐consuming. Herein, we present an alternative approach based on the click reaction between azide and terminal alkyne, which avoids the need to synthesize thiol‐derivatized receptors and is applicable to the heterogeneous morphology of LSPR transducers. The receptors are tethered with an alkyne group, which is considerably simpler than thiolation, while producing a stable product. The transducer surface is modified with a layer of a commercial long‐chain thiol–azide molecule, then clicked with an alkyne‐dertivatized receptor to produce the biorecognition interface. This method is employed for immobilization of four different alkyne‐bearing receptor molecules on Au nano‐island film based LSPR transducers, followed by testing of their performance in biorecognition of specific analytes using LSPR and FTIR spectroscopies. The results establish the usefulness of click chemistry for the preparation of biorecognition interfaces on nanostructured LSPR transducers. Abstract : Click to make it happen : Use of click chemistry for immobilization of alkyne‐tethered receptor molecules on Au nano‐island based localized surface plasmon resonance (LSPR) transducers is demonstrated. The method avoids the complexity involved in the synthesis of thiol‐derivatized receptors, and is applicable to the heterogeneous morphology of LSPR transducers. The results establish the usefulness of click chemistry for the preparation of biorecognition interfaces on nanostructured LSPR transducers.